GENDER REPRESENTATION IN PUNJABI WEDDING TRADITIONS AND SONGS: A QUALITATIVE RESEARCH - Anwar Malik, Iqra; Sarah Shahed; Maryam Zafar (Journal of Arts & Social Sciences, 2024)
AbstractPakistani culture is comprised of multiple traditions and practices that are highly valued and frequently conveyed through music. This study examined the depiction of gender in Punjabi wedding songs, providing a thorough and economical examination of how men and women are portrayed. The study used a qualitative methodology and content analysis to look at song lyrics in order to comprehend how gender roles are portrayed. Twenty participants completed the survey, and 25 well-known Punjabi wedding songs were chosen for analysis from a variety of sources, including books, CDs, DVDs, and internet sites. Four major themes, fourteen sub-themes, and sixty codes pertaining to gender portrayal were found in the content analysis. The results showed that cultural stereotypes predominate, with topics of attachment styles, important connections, and marriage coming in second and third. With a focus on physical characteristics for both sexes, men are usually portrayed as strong and women as lovely. Many aspects of Punjabi society are reflected in the songs, with a special emphasis on relationships. The songs highlighted that important people in a bride's life, including her parents, siblings, and friends, and they emphasize the momentous occasion of moving from her parents' house to her in-laws'. Men are shown as the defenders of women, who are sensitive and treasured. Crucially, there were no examples of women being denigrated or perceived as inferior in the analysis. This study offers insightful information about Punjabi cultural and musical traditions.